Pathogenesis of Hepatocellular Carcinoma: The Interplay of Apoptosis and Autophagy - Elias Kouroumalis; Ioannis Tsomidis; Argyro Voumvouraki (Biomedicines, 2023)
The pathogenesis of hepatocellular carcinoma (HCC) is a multifactorial process that has not yet been fully investigated. Autophagy and apoptosis are two important cellular pathways that are critical for cell survival or death. The balance between apoptosis and autophagy regulates liver cell turnover and maintains intracellular homeostasis. However, the balance is often dysregulated in many cancers, including HCC. Autophagy and apoptosis pathways may be either independent or parallel or one may influence the other. Autophagy may either inhibit or promote apoptosis, thus regulating the fate of the liver cancer cells. In this review, a concise overview of the pathogenesis of HCC is presented, with emphasis on new developments, including the role of endoplasmic reticulum stress, the implication of microRNAs and the role of gut microbiota. The characteristics of HCC associated with a specific liver disease are also described and a brief description of autophagy and apoptosis is provided. The role of autophagy and apoptosis in the initiation, progress and metastatic potential is reviewed and the experimental evidence indicating an interplay between the two is extensively analyzed. The role of ferroptosis, a recently described specific pathway of regulated cell death, is presented. Finally, the potential therapeutic implications of autophagy and apoptosis in drug resistance are examined.